PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2022 - Oktavia, Ami; Nurismalatri (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine whether there is an influence between liquidity (Current Ratio) and solvency (Debt To Assets Ratio) on profitability (Return On Assets) in Food and Beverage Companies listed on the Indonesia Stock Exchange. This study uses a quantitative method in taking financial report data from Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2015-2022. The data collection technique used is secondary sources with library studies and internet research. The results of this study indicate that partially liquidity as measured by the current ratio has no effect on profitability (return on assets) with a significant value of 0.1878> 0.05. While solvency as measured by the debt to assets ratio has a negative and significant effect on profitability (return on assets) with a significant value of 0.0000 <0.05. Based on the results of the simultaneous test (F test) the current ratio and debt to assets ratio together have a significant effect on return on assets with a significant value of 0.000000 <0.05.